Exploring the relevance of spatial scale to life cycle inventory results using environmentally-extended input-output models of the United States. (January 2018) - Yang, Yi; Ingwersen, Wesley W.; Meyer, David E.
Abstract: The accuracy of direct and indirect resource use and emissions of products as quantified in life cycle models depends in part upon the geographical and technological representativeness of the production models. Production conditions vary not just between nations, but also within national boundaries. Understanding the level of geographic resolution within large industrial nations needed to reach acceptable accuracy has not been well-tested across the broad spectrum of goods and services consumed. Using an aggregate 15-industry environmentally-extended input-output model of the US along with detailed interstate commodity flow data, we test the accuracy of regionalizing the national model into two-regions (state - rest of US) versus 51 regions (all US states + DC). Our findings show the two-region form predicts life cycle emissions and resources used within 10–20% of the more detailed 51-region form for most of the environmental flows studied. The two-region form is less accurate when higher variability exists in production conditions for a product. Highlights: The relevance of spatial scale to life cycle inventory results was studied using EEIO models of the US. State-level EEIO models were built at different spatial scales. Results indicate that a simplified 2-region EEIO model roughly approximates the more complicated multi-regional EEIO model.